The Impact of Mitigating Circumstances Procedures: Student Satisfaction, Wellbeing and Structural Compassion on the Campus - Neil Armstrong; Nicola C. Byrom (MDPI AG, 2023)
For several decades, universities have sought to promote better mental health amongst students. For example, universities now have formal institutional arrangements to postpone deadlines for students where there are mitigating circumstances, such as ill health. Such provisions might be understood as praiseworthy cases of institutional compassion. But, empirical research is needed to investigate how these measures play out in practice. This paper draws on ethnographic research in several UK universities to explore the experiences of staff responsible for the enactment of mitigating circumstance provisions. We find staff members sympathetic to the aims of the measures but also sceptical, and in some cases angry, because they find that the provisions have unwanted and undesirable effects. This paper uses the wider social science literature on bureaucracy to consider why this might be the case and raises questions about the capacity of institutions to enact ethical ideals.